Deciphering the combination mechanisms of Gualou–Xiebai herb pair against atherosclerosis by network pharmacology and HPLC-Q-TOF-MS technology - Liu, Yarong; Zhong, Hua; Xu, Pengbo; Zhou, An; Ding, Lidan; Qiu, Jingwen; Wu, Hongfei; Dai, Min (Frontiers in Pharmacology, 2022)
Introduction: Gualou (Trichosanthes kirilowii Maxim)-Xiebai (Allium macrostemon Bunge) (GLXB) is a well-known herb pair against atherosclerosis (AS). However, the combination mechanisms of GLXB herb pair against AS remain unclear. Objective: To compare the difference in efficacy between GLXB herb pair and the single herbs and to explore the combination mechanisms of GLXB against AS in terms of compounds, targets and signaling pathways. Methods: The combined effects of GLXB were evaluated in AS mice. The main compounds of GLXB were identified by HPLC-Q-TOF-MS and UNIFI informatics platforms. The united mechanisms of GLXB in terms of nodes, key interactions and functional clusters were realized by network pharmacology. Finally, the anti-AS mechanisms of GLXB were validated by ELISA and western blot in AS mice. Results: The anti-AS effects of GLXB herb pair (6 g/kg) were more significant than those of Gualou (4 g/kg) and Xiebai (2 g/kg) alone. 48 main components from GLXB herb pair were identified. Besides, GLXB herb pair handled more anti-AS targets and more signaling pathways than Gualou or Xiebai alone, while 10 key targets of GLXB were found by topological analysis. Furthermore, GLXB herb pair (6 g/kg) could obviously suppress the inflammatory targets levels of IL-6, IL-1β, TNF-α, ALOX5, PTGS2 and p-p38 in AS mice. GLXB herb pair (6 g/kg) could also ameliorate endothelial growth and function by regulating the levels of VEGFA, eNOS, p-AKT, VCAM-1, ICAM-1 and reducing macrophage adhesion to vascular wall in AS mice. GLXB herb pair (6 g/kg) could improve the blood lipids levels in AS mice. Besides, the regulating effects of GLXB herb pair (6 g/kg) on levels of IL-1β, TNF-α, ALOX5, VEGFA, eNOS, VCAM-1, ICAM-1 and blood lipids were more significant than those of Gualou (4 g/kg) or Xiebai alone (2 g/kg). Conclusion: The combination mechanisms of GLXB herb pair were elucidated in terms of components, targets and signaling pathways, which may be related to suppressing inflammation, regulating vascular endothelial growth/function and improving blood lipids levels.